Blended Librarians in Academic Libraries: a Brazilian Panorama - de Lima, Gercina Ângela; Moreira dos Santos Macula, Benildes Coura; Bruzinga Borges, Graciane Silva (Revista General de Información y Documentación, 2017)
Academic librarians face challenges that come from the changes caused by the digital environment. These changes are reflected mainly through information and communication technologies that are in constant development and available to users remotely. This article discusses the profile of academic librarians as blended librarians and focuses specifically on the Brazilian context, which is at times in contrast with the international literature about the topic. The characteristics of this professional include the new the role as an educator, in addition to the roles as a manager and as a strategic mediator of information resources. In this new role, the teaching-learning process leads to the development of information literacy of the public. The professionals involved with this new configuration of academic libraries also must be adept at judging the suitability of products and services that are offered to a more demanding, connected, and dynamic public. The results indicate that academic librarians must develop continuously professionally, and be attentive to the demands of the libraries’ community of users, offering services that are specialized and can be remotely accessed.